MAPPING REGIONAL VULNERABILITY TO LEPTOSPIROSIS IN BONDOWOSO REGENCY USING K-MEANS CLUSTER ANALYSIS - Zulfa Auliyati Agustina; Atik Choirul Hidajah; Nur Ali Mas'ud (Universitas Airlangga, 2026)
Leptospirosis cases increased in Bondowoso Regency from 2022 to 2024. However, health interventions for leptospirosis in Bondowoso have not adopted a specific approach based on regional vulnerability levels. Clustering leptospirosis cases is crucial for focusing prevention and control programs. This study aims to analyze the clustering of areas vulnerable to leptospirosis based on risk factors in Bondowoso Regency. This study employed a quantitative design using the K-Means method for clustering. The research variables included the number of disasters, the proportion of male residents, the proportion of farmers, elevation, the number of markets, the number of temporary waste disposal sites (TPS), and the proportion of vegetated land. Cluster analysis was conducted using SPSS. The results revealed three vulnerability clusters: high risk (3 districts), moderate risk (17 districts), and low risk (3 districts). The variables that distinguished the clusters were the number of TPS (F=22.266, p=0.000), the number of disasters (F=6.047, p=0.009), the number of markets (F=5.367, p=0.014), elevation (F=5.388, p=0.013), the proportion of farmers (F=5.007, p=0.017), the proportion of male residents (F=.318, p=0.028), and the proportion of vegetated land (F=3.900, p = 0.037). In conclusion, vulnerability to leptospirosis in Bondowoso is influenced by a combination of environmental, infrastructural, and demographic factors, with sanitation being the most dominant. Centralized waste management, disaster mitigation, and strengthened area-based surveillance are necessary to achieve more effective prevention and control of leptospirosis.